Measuring Cerebrovascular Reactivity: Sixteen Avoidable Pitfalls - Sobczyk, Olivia; Fierstra, Jorn; Venkatraghavan, Lakshmikumar; Poublanc, Julien; Duffin, James; Fisher, Joseph A.; Mikulis, David J. (Frontiers in Physiology, 2021)
An increase in arterial PCO2 is the most common stressor used to increase cerebral blood flow for assessing brain vascular reactivity. That CO2 is readily obtained, inexpensive, easy to administer, and safe to inhale belies the difficulties in extracting scientifically and clinically relevant information from the resulting flow responses. Over the past two decades we have studied about 2000 individuals, most with cervical and cerebral vascular pathology. The ability to deliver different forms of precise hypercapnic stimuli enabled systematic exploration of the blood flow-related signal changes. Insights (often serendipitous) gained from the vascular responses to these stimuli acted as guides for optimizing stimulus design, thereby leading to improvements in our interpretation of the underlying physiological and pathophysiological processes. Here we present our accumulated insight as sixteen “lessons learned”.